Parent's attitude toward use of internet for child's oral health and treatment - Gyanendra Kumar; Aditi Garg; Mridula Goswami; Ferah Rehman; Ravita Bidhan (Wolters Kluwer Medknow Publications, 2020)
Background: Widespread use of internet in the modern era has allowed increased access to seek medical and dental education by self-education. However, limited evidence is reported regarding the use of internet to gather oral health information by patients reporting to dental hospital in a centrally located institute of New Delhi, India. Aim: The aim of the present cross-sectional study was to evaluate the parental attitude toward the use of internet related to child's oral health and treatment. Design: The data was collected from 500 patients from the Outpatient Department of Pedodontics and Preventive Dentistry, Maulana Azad Institute of Dental Sciences, New Delhi. A self-administered questionnaire with open ended questions assessing parental attitude toward the use of internet for oral health information was designed, and patients willing to participate were included. Materials and Methods: The present cross-sectional study was conducted among 500 parents selected randomly from the Out Patient Department. The participants were given the questionnaire which assessed their attitude towards use of internet related to child's oral health and treatment. The data was collected and statistical analysis was performed. Results: 86% reported to have high school education, 7% to have middle school education, 3% to be diploma holders, 2% to be graduates and postgraduates, and only 2% as professionals. 56.1% of the participants use internet to gather information on oral health, whereas only 41.9% reported that they have access to internet but do not use to search information related to oral health and disease. 26.1% of the participants often search information on internet before consulting a doctor, and 29.3% discuss treatment plan after searching from internet with their doctor. Conclusion: Since the use of internet by younger adults seeking information on oral health seems to be more prevalent among educated people, less prevalence is reported in this study. Majority of the participants were aware regarding the harmful effects of such information and also reported that treatment or medication searched on internet made their problem worse than before.